Feasible Options for Behavior Change Toward More Effective Ocean Literacy: A Systematic Review - Stoll-Kleemann, Susanne (Frontiers in Marine Science, 2019)
Effective ocean literacy requires appropriate individual behavior, but achieving this – based on behavior change - is extremely difficult. Social-psychological research shows that even generating knowledge and awareness towards protecting the environment - including the oceans - very rarely produces behavior change. The correlation between knowledge and behavior change is demonstrably surprisingly low. Based upon a systematic interdisciplinary literature review, this article evaluates the factors constituting behavior that are important for ocean literacy. Furthermore, it includes an analysis of options for individual behavior change. The literature review covers research and theories from behavioral sciences such as social, environmental, and emotional psychology, as well as from other social sciences. Specifically, research on pro-environmental behavior is evaluated and applied to the specific case of ocean-related behaviors and ocean literacy. As a result, the model of pro-environmental behavior by Kollmuss and Agyeman has successfully been transferred to increase the effectiveness of ocean literacy because it considers internal (e.g. emotions and values) and external factors (e.g. politico-economic and socio-cultural), which are crucial to achieve behavior change. Further results show that the theoretical analysis of different influence factors of ocean related behavior help to identify options to enhance ocean literacy, partially not yet broadly applied in this field, such as reputation-based incentives, social marketing, and successfully diffusing social change, which is illustrated within two examples of success stories. Nevertheless, improvements remain challenging due to barriers identified on the individual level (e.g. cognitive dissonance and moral disengagement) and adverse political and economic power relations in light of rapidly increasing environmental problems in our oceans.